PENERAPAN METODE THINK PAIR SHARE DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD 167644 TEBING TINGGI - Nurmala . (FIP Unimed, 2015)
ABSTRACT This aim of this research is to improve learning result on Indonesian langauge subject through think pair share method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SDN 167644 Tebing Tinggi which amounted to 35 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the think pair share method of Indonesian language subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (68,57%), the first cycle (77,14%), cycle II (91,42 %) and complete learn the clasical equal to 91,42 %. Key word : Think Pair Share, Learning result